2022
DOI: 10.1002/ccr3.6054
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe low back pain with a focused vibro‐percussion wave treatment: A case report

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…On MRI imaging, the lumbar spine showed improvement. (Desmoulin G et al, 2007) Another study has revealed that the effect of sound waves on musculoskeletal is not only consequences in decline of pain and keeping alignment of spine but also comprises elevated key proteins for spinal well-being and providing a suitable environment for cells that promotes ligament repair (Alsalamah & Bartel, 2022). KKT is an effective way of treating low back pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On MRI imaging, the lumbar spine showed improvement. (Desmoulin G et al, 2007) Another study has revealed that the effect of sound waves on musculoskeletal is not only consequences in decline of pain and keeping alignment of spine but also comprises elevated key proteins for spinal well-being and providing a suitable environment for cells that promotes ligament repair (Alsalamah & Bartel, 2022). KKT is an effective way of treating low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…No opposing effects associated to the treatment were practiced by the patient. (Alsalamah & Bartel, 2022) A study on Forty eight subjects conducted that includes 28 male and 20 female, were engaged. The ages of these subjects were between 18 and 77 and had a repeated history of fluctuating levels of lessening low-back-pain.…”
Section: Discussionmentioning
confidence: 99%
“…One example of an emerging treatment modality is the use of vibratory stimuli as a form of neuromodulation, which has shown promise in treating symptoms of Alzheimer’s [ 136 , 137 ], Parkinson’s [ 138 , 139 ] and depressive disorders [ 140 , 141 ]. Vibratory stimuli, especially those focused on stimulating the spine, have also emerged as a promising new treatment modality when applied to treat cLBP [ 142 , 143 , 144 , 145 ]. These waveforms have also demonstrated changes in proteoglycan expression within the intervertebral discs, showing a possible mechanistic influence on spinal structures [ 146 , 147 ].…”
Section: Neurodegenerative Changes In the Brainmentioning
confidence: 99%